Missense mutation of angiotensin converting enzyme gene in an Alzheimer’s disease patient: a case report - He, Mingyue; Zhang, Fan; Qi, Jing; Zhang, Wei (Frontiers in Neuroscience, 2024)
Alzheimer’s disease (AD) is the most common type of cognitive impairment in the elderly. In this report, we presented a case of a 52-year-old woman with rapid disease progression within 6 months. She was diagnosed with mild dementia according to the clinical symptoms and neuropsychological assessment results. Based on the results of neuropathological proteins in cerebrospinal fluid, cranial magnetic resonance imaging, and positron emission tomography/computed tomography, the patient showed the presence of β amyloid deposition, pathologic tau along with neurodegeneration [A+T+(N+)], indicative of AD. Whole exome sequencing revealed a heterozygous C-to-T missense mutation of nucleotide 3,755 (c.3755C > T) in exon 25 of the angiotensin converting enzyme (ACE) gene on chromosome 17q23 (rs762056936).